Comprehending the dynamism of B chromosomes in their journey towards becoming unselfish - Rajpal, Vijay Rani; Sharma, Suman; Sehgal, Deepmala; Sharma, Prashansa; Wadhwa, Nikita; Dhakate, Priyanka; Chandra, Atika; Thakur, Rakesh Kr.; Deb, Sohini; Rama Rao, Satyawada; Mir, Bilal Ahmad; Raina, Soom Nath (Frontiers in Cell and Developmental Biology, 2023)
Investigated for more than a century now, B chromosomes (Bs) research has come a long way from Bs being considered parasitic or neutral to bringing benefits to their hosts. Bs exist as accessory chromosomes along with the standard A chromosomes (As) across eukaryotic taxa. Represented singly or in multiple copies, Bs are largely heterochromatic but also contain euchromatic and organellar segments. Although Bs are derived entities, they follow their species-specific evolutionary pattern. Bs fail to pair with the standard chromosomes during meiosis and vary in their number, size, composition and structure across taxa and ensure their successful transmission through non-mendelian mechanisms like mitotic, pre-meiotic, meiotic or post-meiotic drives, unique non-disjunction, self-pairing or even imparting benefits to the host when they lack drive. Bs have been associated with cellular processes like sex determination, pathogenicity, resistance to pathogens, phenotypic effects, and differential gene expression. With the advancements in B-omics research, novel insights have been gleaned on their functions, some of which have been associated with the regulation of gene expression of As through increased expression of miRNAs or differential expression of transposable elements located on them. The next-generation sequencing and emerging technologies will further likely unravel the cellular, molecular and functional behavior of these enigmatic entities. Amidst the extensive fluidity shown by Bs in their attributes, we perceive that the existence and survival of Bs in the populations most likely seem to be a trade-off between the drive efficiency and adaptive significance versus their adverse effects on reproduction.